Pembelajaran Daring: Masihkah Membuat Mahasiswa Stres, Cemas, dan Depresi? - zakiyah, zakiyah; Marianna, Siswani; A, MellaYuria R; Wulandari, Latiffa Ihza; Ramadhani, Nabilah (Jurnal Kesehatan, 2023)
Online learning is implemented and carried out with various strategies which are often accompanied by assignments that those assignments are often should be completed at the same time, causing stress, anxiety and even depression for students. The research aim is to analyse the impact of the application of online learning to the levels of stress, anxiety, and depression in students. The research method used a descriptive correlation design with a cross-sectional approach. Research instruments are: 1) online learning implementation questionnaire; and 2) Depression Anxiety Stress Scale (DASS) 42. The research sample was 328 students from 11 study programs at Binawan University who met the inclusion criteria using a simple random sampling technique. The results of research on the implementation of online learning were at a good level (75%), the majority of students' depression levels were at normal depression levels (56.1%), students' anxiety levels were mostly at normal levels (33.2%), and students' stress levels were also mostly at normal levels (66.8%), with a p-value of the correlation between online learning and depression level is 0.12 (>0.05), online learning and an anxiety level is 0.2 (>0.05), and online learning with stress level is 0.01 (< 0.05). The conclusion is that there is no relationship between the application of online learning and levels of depression and anxiety, and there is a relationship between online learning and the stress levels of students at Binawan University. It is suggested to improve and develop more effective online learning strategies and systems for students, and there is a need to do a stress management training for students so they can adapt better in dealing with stressors during online learning.